Bahasa Inggris: Bahasa Inggris - Wahyuningsih, Retno; Darni, Joyeti; Abdi, Lalu Khairul (Journal of Local Therapy, 2024)
Background: Physical changes in the elderly include changes in the aorta and systemic blood vessels that affect blood pressure. Increased blood pressure in the elderly is a health problem that must be handled properly. The management of hypertension can be done by giving the DASH diet, in this case this study provides an interlude to the DASH diet. Research Methods: This type of research uses a quasi-experimental research design with a randomized pre-test-post-test control group design. Subjects were divided into two groups, namely the treatment group and the control group.Research Results: Most of the subjects in this study were elderly aged 70-74 years (33.3%) in the treatment and 75-80 years (50%) in the control. The research subjects were mostly female, namely 27 elderly (75%). The average body weight for the treatment group was 54.24 kg and the control group was 48.48 kg. The mean blood pressure in both groups before the intervention was higher than the mean blood pressure after the intervention. The results of the paired-t test statistic showed that there was a difference in the mean of systolic (0.000) and diastolic (0.000) blood pressure before and after the intervention. Meanwhile, the two-group difference test showed that there was no difference in systolic and diastolic blood pressure before the intervention. However, after the intervention, there was a difference in systolic and diastolic blood pressure. Furthermore, there was an effect of the DASH diet interlude on Systolic blood pressure (p = 0.000) and Diastolic blood pressure (p = 0.034) after the DASH diet snack was given.Conclusion: there is an effect of giving a DASH diet interlude on systolic blood pressure (p=0.000) and diastolic blood pressure (p=0.034) after giving the DASH diet snack.